2009
DOI: 10.1159/000272029
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction of C57BL/6 Mouse Inner Ear during Development

Abstract: Purpose: To explore the three-dimensional (3-D) morphological characteristics of the complicated inner ear development of the C57BL/6 mouse. Methods: Specimens of C57BL/6 mouse embryos on days E7.5, E8.5, E9.5, E10.5, E11.5, E12.5 and E14.5 were collected and sectioned serially in this experiment. After hematoxylin and eosin staining, parts of the inner ear were pictured under the microscope with specific positional control. Using the protocol of 3D-DOCTOR software, we outlined the inner ear margin including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We found that Greb1l expression is widespread, and not highly compartmentalized during craniofacial development, and peaks at E8.5 and E13–E16, after which it declines during adulthood (Fig 2). In mice, the inner ear rises from a thickening of the ectoderm known as the otic placode at E7.5, and at E8.5 the otic placode invaginates to form the otocyst (Chi et al 2009). At E9.5, the otocyst has closed and from here on to E14.5, complex and rapid morphological changes occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Greb1l expression is widespread, and not highly compartmentalized during craniofacial development, and peaks at E8.5 and E13–E16, after which it declines during adulthood (Fig 2). In mice, the inner ear rises from a thickening of the ectoderm known as the otic placode at E7.5, and at E8.5 the otic placode invaginates to form the otocyst (Chi et al 2009). At E9.5, the otocyst has closed and from here on to E14.5, complex and rapid morphological changes occur.…”
Section: Discussionmentioning
confidence: 99%
“…During this time-frame the mature inner ear structure is formed, which is comprised of the semicircular canals, vestibule, and cochleae. At E12.5, all primordial structures have undergone further refinements, approximating their mature shape, and at E14.5, the membranous labyrinth has attained its mature shape, and the cochlea has reached one and a half turns (Chi et al 2009). We show that Greb1l peaks in the very early development of the inner ear (E8.5 otic placode invagination), later in the maturing and the refinement of the formed cochlear, and vestibular shapes (E13–E16), supporting a possibly important role in early ear development.…”
Section: Discussionmentioning
confidence: 99%